The use of steelmaking slags and fly ash in structural mortars. (1st March 2016) - Santamaría, Amaia; Rojí, Eduardo; Skaf, Marta; Marcos, Ignacio; González, Javier J.
Highlights: Mortars containing up to 75% by dry weight of steelmaking slag have successfully been prepared. The use of electric arc furnace slag increases the strength and the density of mixes. Air-entrainment admixtures could be problematic for use in slag mortars. The use of ladle furnace basic slag must be carefully monitored in mortars. Abstract: The main objective of this work is to produce structural slag mortars of good mechanical strength and workability, while reducing the consumption of Portland clinker, the production of which is a growing source of environmental concern. In this context, the study looks at the preparation of these mortars with steelmaking slags (electric arc furnace slag, ladle furnace slag) in partial substitution of conventional aggregates, and as supplementary cementing materials, and the use of Portland cement that includes a notable proportion of fly-ash. A detailed examination of the characteristics of eight mortar mixes is described. Structural and mechanical analyses are performed on the mixes, to study the role of water-reducer and air-entrainment admixtures; also, shrinkage contraction and other volumetric variations of the mixtures are measured and evaluated. The long-term behavior of these slag mixes appeared acceptable, thereby opening a promising line of work that will eventually establish suitable conditions for their use. The strength-to-weight ratio of these mortars is encouraging although uncertainty persists over the use of air-entrainment admixtures and ladle furnace slag.